(untitled) (VETERINARIA, 2023)
This research aims to make a vaccine from Edwardsiella ictaluri isolated from local isolate. It was carried out at Aquaculture Laboratory of Aquaculture Department, Sriwijaya University. Bacterial isolate was a stock from Fish Quarantine and Inspection Agency, South Sumatera, Indonesia. Before vaccination, fish had already adapted to pellets and aquaria conditions. After 14 days post-vaccination (dpv) catfish was infected by E. tarda 107 CFU.ml-1 administrated by injection. The result revealed that vaccination can protect fish from edwardsiellosis better than non-vaccinated fish with Relative Percent Survival (RPS) value was 63.64 % and antibody titer increased from 7 dpv and greater at 14 dpv. In fact, the RPS value was less than 70% but there were no hematological disorders after vaccination. It means the whole cells vaccine can be used as a vaccine candidate to protect striped catfish from edwardsiellosis. Furthermore, some experiments need to be developed to increase RPS value in the future.